Construction of high-nuclear 4p–4f heterometallic Ln11Ge12 cluster-organic frameworks with high-sensitivity luminescence sensing of Fe3+ in aqueous solution. Issue 48 (19th November 2020) - Li, Leilei; Cai, Bin; Pang, Donghui; Du, Xinxin; Yin, Xingliang; Wang, Huaiwei; Yang, Jie; Li, Dacheng; Dou, Jianmin
Abstract : The [Pr11 Ge12 ] 4p–4f cluster-organic framework shows highly selective and sensitive sensing of Fe 3+ in aqueous solution. Abstract : Heterometallic cluster-organic frameworks with fascinating architectures and multi-functionality have the potential to be applied in various fields. However, in comparison with p–d, d–d, and d–f heterometallic cluster-organic frameworks, p–f heterometallic cluster-organic frameworks are far less explored even though they possess multiple merits. Herein, two novel isomorphic 4p–4f heterometallic cluster-organic frameworks based on high-nuclear [Ln11 Ge12 ] (Ln = Pr, L1 and Nd, L2 ) second building units have been successfully synthesized via a hydrothermal approach by using bis(carboxyethylgermanium) sesquioxide (H2 E2 Ge2 O3, E = –CH2 CH2 COO–). The [Ln11 Ge12 ] cluster is constructed with two Ln-capped Ge6 -rings sandwiching a gear-like [Ln9 ] unit. The as-prepared 4p–4f heterometallic [Ln11 Ge12 ] cluster-organic frameworks possess two-dimensional (2D) layered structures. Moreover, the property study reveals the selective and sensitive luminescence sensing of Fe 3+ with L1, exhibiting its promising application in environmental monitoring.